Predicting the response of three common subtropical tree species in China to climate change - Jin, Songheng; Chi, Yi; Li, Xueqin; Shu, Pengzhou; Zhu, Mengxun; Yuan, Zheng; Liu, Yang; Chen, Wenjing; Han, Yini (Frontiers in Forests and Global Change, 2023)
Introduction Climate is crucial factor influencing species distribution, and with global climate change, the potential geographic distribution of species will also alter. In this study, three subtropical tree species (Cunninghamia lanceolata, Pinus taiwanensis, and Quercus glauca) of great ecological values were selected as research objects. Methods We applied a maximum entropy (MaxEnt) to predict their potential distributions under different climate scenarios in both present and future conditions based on 37 environmental factors. Jackknife test was used in key factors affecting species distribution. In addition, we explored the key environmental variables that affect their distributions and revealed the evolutionary patterns and migration trends of these tree species under future climate. Results The main findings are as follows: (1) Winter temperature, winter precipitation, and annual temperature range are identified as the key environmental variables affecting the potential geographic distribution of the three tree species; moreover, precipitation-related factors have a greater impact than temperature-related factors; (2) Currently suitable habitats for these three tree species are primarily located in subtropical China with decreasing suitability from south to north; (3) Under future climate conditions, the area of potentially suitable habitat for C. lanceolata continues to expand, while P. taiwanensis and Q. glauca tend to experience a reduction due to increasing greenhouse gas emissions over time; and (4) The centroid of suitable habitat for C. lanceolata shifts northward under future climate change, while the centroid of P. taiwanensis and Q. glauca move southward along with shrinking suitable habitat area. Discussion Our predictions highlight a high risk of habitat loss of Q. glauca under climate change, recommending management and conservation references for these three commonly used afforestation species under current and future climate change scenarios in China.